Penerapan Media Pembelajaran Berbasis Aplikasi Canva dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Peserta didik Kelas VII SMP Muhammadiyah 1 Bontang Tahun Pelajaran 2024-2025 - Hasmiati, Hasmi (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
The objective of this study is to examine the implementation of Canva-based instructional media in enhancing learning outcomes in Islamic Religious Education (IRE). This research employs a qualitative method with a descriptive approach. The subjects of the study are seventh-grade students at SMP Muhammadiyah 1 Bontang during the 2024/2025 academic year. Datawere collected through observation, interviews, self-assessment, and documentation. The data analysis process involved data reduction, data presentation, and drawing conclusions. The findings indicate that the use of the Canva application as a learning medium has a positive impact on improving student performance in IRE. This media helps present instructional material in a more engaging and accessible way for students. The improvement can be seen in students' conceptual understanding, the strengthening of faith-based values, moral development, the relevance of content to everyday life, the enhancement of critical thinking skills, and the ability to apply theoretical knowledge in practice. Therefore, Canva can be considered an effective alternative learning tool to support the optimal delivery of Islamic Religious Education.